Tantangan Auditor dalam Meninjau Kewajaran Akun Utang Wesel dan Modal - Danang Valpareza Faturrachman; Muhammad Faiz Adzikra Herwandi; Muhammad Rayhan; Ridwan Zulpi Agha (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
This study examines the challenges encountered by auditors in evaluating the fairness of notes payable and equity accounts as part of the financial statement audit process. These accounts carry a high risk of misstatement when recognition, measurement, or disclosure does not align with applicable standards. The purpose of this research is to provide an in-depth overview of the procedures, techniques, and professional judgments applied by auditors in assessing the fairness of both accounts, including issues related to misclassification, incomplete audit evidence, and limited responses from third-party confirmations. This study employs a descriptive qualitative method through a literature review of relevant academic publications. The findings indicate that auditors frequently face obstacles such as the mixing of accrued interest with the principal amount, low confirmation response rates, and inadequate supporting documentation. These challenges require auditors to perform alternative procedures and strengthen substantive testing to obtain sufficient and appropriate audit evidence. The implications of this study highlight the need for consistent application of auditing standards, comprehensive documentation, and effective communication with clients to ensure financial statements present a true and fair view.